2020
DOI: 10.3390/environments7060046
|View full text |Cite
|
Sign up to set email alerts
|

New Insights into Cellular Impacts of Metals in Aquatic Animals

Abstract: Toxic metals remain a current important threat to aquatic ecosystems, despite regulatory efforts to reduce their release. Several toxic metals already appear in the list of priority substances polluting surface waters, while concerns arise from the increasing use of technology-critical metals such as metallic nanoparticles, rare-earth, and platinum group metals. In aquatic environments, various chemical, biological and physical processes determine the impact of metals on the biota. This review provides insight… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 82 publications
(114 reference statements)
0
14
0
Order By: Relevance
“…Metals, and in particular copper, are able to induce oxidative stress in bivalves. Cu 2+ generates free radicals through the Fenton and Haber-Weis reaction [44]. Cu 2+ -exposed haemocytes showed a remarkable increase in reactive oxygen species production, which induced oxidative stress in mussel Perna canaliculus [10].…”
Section: Inflammation Oxidative Stress Defence and Lipid Metabolismmentioning
confidence: 99%
See 1 more Smart Citation
“…Metals, and in particular copper, are able to induce oxidative stress in bivalves. Cu 2+ generates free radicals through the Fenton and Haber-Weis reaction [44]. Cu 2+ -exposed haemocytes showed a remarkable increase in reactive oxygen species production, which induced oxidative stress in mussel Perna canaliculus [10].…”
Section: Inflammation Oxidative Stress Defence and Lipid Metabolismmentioning
confidence: 99%
“…The results of in vivo experiments, after 3 days exposure to Cu 2+ at 40 µg/L, indicated that the inhibition of hexokinase would be caused, on the one hand, by a direct binding of the metal to the sulfhydryl groups of the protein, and on the other hand, more indirectly, by a decrease in the level of reduced glutathione (GSH) and consequent imbalance between pro-oxidant and antioxidant cellular processes. Indeed, GSH is used by metal exposed organisms to protect themselves against their cytotoxicity [44].…”
Section: Energy Metabolism and Oxygen Transportmentioning
confidence: 99%
“…Molecular biomarkers such as gene transcripts have been proposed to capture responses upstream of adverse effects on the organism level (Calzolai et al, 2007; Piña et al, 2007). Some transcripts may be specific to certain toxicants or biological effects, whereas others, including responses involved in toxicant metabolism, oxidative stress, and general cytoprotection, are considered potential biomarkers of general toxicity and chemical stress (Le Saux et al, 2020; Sulmon et al, 2015). Many studies on transcriptional biomarker candidates are, however, based on single or few exposure groups and/or pooled samples from multiple individuals.…”
Section: Introductionmentioning
confidence: 99%
“…By addressing response trends to both general and continuous exposures (concentration and time), our objective was to evaluate the overall responsiveness of transcriptional biomarker candidates of general toxicity and chemical stress. Specifically, we selected metal exposures to represent general toxicity and a specific set of transcripts (catalase [ cat ], gst , hsp70 , hsp90 , mt , and sod ) that represent common biomarkers of nonspecific chemical stress (Le Saux et al, 2020; Miao et al, 2015; Sulmon et al, 2015). To account for individual variation while also reducing the variability of experimental exposures, we limited the analysis to include controlled laboratory studies where transcriptional responses were measured on the individual level.…”
Section: Introductionmentioning
confidence: 99%
“…Antioxidant systems in aquatic organisms are low molecular weight ones such as glutathione (GSH), ascorbic acid, and carotenoids (Lauritano and Ianora, 2020). Deficiency or excess of some trace elements such as selenium, copper, zinc affects antioxidant systems (Le Saux et al, 2020).…”
Section: Introductionmentioning
confidence: 99%